How sustainable marketing influences the customer engagement and sustainable purchase intention? The moderating role of corporate social responsibility - Gong, Yanping; Xiao, Jun; Tang, Xiuyuan; Li, Jinglu (Frontiers in Psychology, 2023)
Today's civilization faces serious challenges related to sustainability. Without the support of society, organizations can no longer continually build their enterprises. The pressure of sustainable development goals are also enhancing on companies. Thus, marketing managers place a strong emphasis on meeting the socio-ethical demands of their target audience, whether it is through cultural promotion, environmental conservation, or disaster relief initiatives. The topic of how to successfully carry out an organization's economic, social, and environmental duties is raised by sustainability. For data collection, a self-administered questionnaire was distributed to 393 purchasers and potential purchasers of electric vehicles, and a structural equation model (SEM) test was conducted using Mplus 8.0 software. The results of the study showed that: First, the outcome states that sustainable marketing valuable for improving brand image. Second, brand image is good for customer engagement in the Chinese market for electric automobiles. Third, the appeal of sustainable purchasing intentions is increased by brand image. Fourth, a useful instrument for long-term purchase intentions is customer engagement. Fifth, CSR has a significant role in enhancing consumers' intentions to make sustainable purchases. Most notably, it acts as a helpful moderator in the relationship between company image and customer engagement. Lastly, CSR also strengthens the link between company image and sustainable purchasing intentions. This research offers a theoretical framework and practical implications that sustainable marketing initiatives are an important antecedent of organizational outcomes for the electric vehicle sector in China.